The King, the Junta and the “Impartial Broker”: A microscopic approach to the Johnson-Constantine meeting on 11 September 1967 - Kallivretakis, Leonidas (The Historical Review/La Revue Historique, 2018)
This article explores the relations between the Greek military regime and King Constantine, as they evolved during the first months after the April 1967 coup, focusing on the part played by the “American factor”. Tracing step-by-step Constantine’s contacts with US officials, from his conversations with the American Ambassador in Athens to his meeting with President Johnson, the author investigates the King’s perception of the US government’s position regarding a possible confrontation between him and the colonels and how that perception influenced Constantine’s final decision to launch a counter-coup in December 1967.